Forcefield evaluation and accelerated molecular dynamics simulation of Zn(II) binding to N-terminus of amyloid-β. (August 2021) - Al-Shammari, Nadiyah; Savva, Loizos; Kennedy-Britten, Oliver; Platts, James A.
Graphical abstract: Accelerated molecular dynamics is used to explore the binding of Zn the N-terminal fragment of amyloid-β, and to test the performance of AMBER-style forcefields. Highlights: AMBER forcefield reproduces NMR structure of Zn(II) bound to N-terminal fragment of Aβ. Implicit solvent performs at least as well as explicit in this regard. Accelerated MD shows subtle difference in structure and dynamics for different binding modes. Free energy surface shows restriction in size and flexibility due to Zn-binding. Abstract: We report conventional and accelerated molecular dynamics simulation of Zn(II) bound to the N-terminus of amyloid-β. By comparison against NMR data for the experimentally determined binding mode, we find that certain combinations of forcefield and solvent model perform acceptably in describing the size, shape and secondary structure, and that there is no appreciable difference between implicit and explicit solvent models. We therefore used the combination of ff14SB forcefield and GBSA solvent model to compare the result of different binding modes of Zn(II) to the same peptide, using accelerated MD to enhance sampling and comparing the free peptide simulated in the same way. We show that Zn(II) imparts significant rigidity to the peptide, disrupts the secondary structure and pattern of salt bridges seen in the free peptide, and induces closer contact between residues. Free energy surfaces in 1 or 2 dimensions further highlight the effect of metal coordination on peptide's spatial extent. We also provide evidence that accelerated MD provides improved sampling over conventional MD by visiting as many or more configurations in much shorter simulation times.